A problem of synthesis of nano-optical elements for the formation of dynamic images - Goncharsky, A.A.; Durlevich, S.R. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
The inverse problems of synthesis of nano-optical elements for the formation of dynamic images that change their position as the flat optical element is tilted are considered. The inverse problem of computing the microrelief of nano-optical elements is solved in the framework of the Fresnel scalar wave model. The microrelief is formed using the electron-beam lithographic technology. Nano-optical elements with dynamic effects are used to protect documents against counterfeiting.